Assessment of Antioxidant Activity, Total Phenolic and Flavonoid Contents of Albizia saponaria L. Bark Extract - Lukman, Lukman; Rosita, Noorma; Widyowati, Retno (Science and Technology Indonesia, 2024)
Langir (Albizia saponaria L.), belonging to the family of the Fabaceae, is a medicinal endemic plant of South Sulawesi, Indonesia. The Albizia genus shows antioxidant, antibacterial, anthelmintic, antidandruff, and anti-inflammatory properties. In this study, total phenolic (TP) and total flavonoid (TF) extracts from the bark of A. saponaria were screened for robust antioxidant activity in order to identify potential sources of new compounds for use in pharmaceutical formulations in the future. TP and TF of the 96% ethanol extract and fractions (hexane, ethyl acetate, butanol, and water) were calculated by the Folin–Ciocalteu and aluminum chloride procedures, respectively. Furthermore, the antioxidant activity was determined by DPPH free radical scavenging method and ABTS assay. Generally, both extract and fractions showed significant radical scavenging activities. Ethyl acetate fraction exhibited more potent radical scavenging activity in the DPPH method (IC50 35.27 ± 2.85 µg/mL) and ABTS assay (IC50 60.04 ± 0.98 µg/mL), followed by 96% ethanol extract, and hexane, butanol, and water fractions. Furthermore, the highest TP (4.50 ± 0.01 mg/g GAE) and TF (3.55 ± 0.04 mg/g QE) were obtained from ethyl acetate fraction. There was a strong correlation between antioxidant activity with TP (DPPH, R2 = 0.6436; ABTS, R2 = 0.7676) and TF content (DPPH, R2 = 0.5533; ABTS, R2 = 0.5961). The extract’s antioxidant properties may be attributable to its higher phenolic and flavonoid content. In summary, the phenolic and flavonoid content of the ethyl acetate fraction indicates its potential utility as a source of antioxidants.